Accumulation Regimes in Dynastic Economies with Resource Dependence and Habit Formation - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
We analyze the consequences of habit formation for income levels and long-term growth in an overlapping generations model with dynastic altruism and resource dependence. If the strength of habits is below a critical level, the competitive economy displays an altruistic (Ramsey-like) equilibrium where consumption sustainability obeys the Stiglitz condition, and habits yield permanent effects on output levels due to transitional effects on growth rates, capital profitability and speed of resource depletion. If the strength of habits is above the critical threshold, the economy achieves a selfish (Diamond-like) equilibrium in which habits increase growth rates and resource depletion even in the long run, sustainability conditions are less restrictive, consumption and output grow faster than in Ramsey equilibria, but welfare is much lower. Results hinge on resource dependence, as different depletion rates modify the intergenerational distribution of wealth and thereby the growth rate attained in either equilibrium.
Keywords: Q30; D91; E21; 330; Dynastic Altruism; Overlapping Generations; Capital-Resource Model; Habit Formation; Altruismus; Privater Konsum; Intertemporale Entscheidung; Wirtschaftswachstum; Overlapping Generations; Theorie